COMPILING BEST PRACTICE STORIES USING THE STAR METHOD (SITUATIONS, CHALLENGES, ACTIONS, REFLECTION OF RESULTS AND IMPACTS) RELATED TO THE EXPERIENCE OF OVERCOMING STUDENT PROBLEMS IN LEARNING - Ni Made Suputri (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2024)
This research aims to increase the learning motivation of students in class X AP 1 SMK Negeri 3 Sukawati through the application of the Problem Based Learning (PBL) learning model to resource scarcity materials. In this context, low student learning motivation is identified as a major challenge, which is influenced by social environmental factors and less innovative teaching methods. The implementation of PBL is carried out by preparing learning tools that include teaching modules, learning media, and assessment instruments. The results of the study showed that the application of the PBL model succeeded in improving student activities and learning outcomes, with an average cognitive score of 86.52. There were 21 out of 23 students who achieved learning completion. The conclusion of this study is that the application of the PBL model is effective in improving student motivation and learning outcomes, with recommendations to continue to develop learning plans that are in accordance with the characteristics of students and materials.